Research on Conducted EMI Noise Diagnosis Method based on Infomax-WT Algorithm (Global Journal of Science Frontier Research, 2020)
In this paper, a diagnostic method of conducted EMI noise based on the Infomax-WT algorithm is proposed. Using collected conductive EMI noise samples, several independent noise signals are separated by Infomax. Each noise signal is subjected to wavelet transform to obtain the time-frequency diagram of each noise signal. The noise source is determined according to the frequency characteristic obtained by the time-frequency chart. Finally.
Keywords: electromagnetic compatibility; infomax algorithm; wavelet transform; conducted interference; noise diagnosis